ULUM Journal of Religious Inquiries 1/2 (December 2018) - Harun Çağlayan (ULUM, 2018)
Dear Readers, we present the second issue of ULUM to you.As ULUM team, we are rightly proud of taking another step in reaching our target in the international platforms where scientific knowledge is shared. In order to contribute more to the world of science, we develop our infrastructure with strong investments and expand our staff with new academicians.The civilization has only developed by adhering to its principles of intercultural interaction, quality standard and reliability. In this context, as ULUM journal, we have been trying to present the knowledge produced in the field of social sciences, especially in Muslim culture, to the common gains of humanity.Since ULUM journal has already begun to be scanned by leading international indexes, it attracts attention of researchers from different countries. We try to be worthy of the expectations of the scientific world by selecting the scientific articles with the necessary conditions from among the submitted articles. With this understanding, we present to you our new issue including valuable articles, which are carefully selected and completed peer review process successfully.In general, the articles are related to studies that focus on different aspects of social and religious issues. Before leaving you alone with these valuable articles, I would like to thank the valuable writers, reviewers and editorial board members who contributed to the preparation of this issue and to present our love and respect to our readers. I wish you all an enjoyable reading with our new issue with the hope that will be useful for the common future of humanity.